Análisis y Elaboración de un Manual de Descripción, Valoración y Clasificación, del Talento Humano en el Gobierno Autónomo Descentralizado Municipal del Cantón Saraguro - Torres Torres, Milton de Jesús (2016)
This research consists of a brief problem, which is able to identify some of the weaknesses that contain Human Talent of GAD Saraguro city, its purpose is centered in the analysis and development of a manual description and valuation and classification of Human Talent Decentralized Autonomous Government the city of Canton Saraguro. Allowing proper placement of human resources according to the functions and processes governed by the labor code and LOSEP. The general objective proposes the analysis and proposal of a Manual of Description, Valuation and Classification of Posts for Decentralized Autonomous Government of the Canton Saraguro that allow institutional development and the development of human talent with efficiency and quality. While specific objectives are related to:  Develop a situational analysis of human talent in the Municipal Decentralized Autonomous Government of the Canton Saraguro.  Identify the roles of 166 officials and workers in each job for the development of a manual for municipal functions to the Municipal Decentralized Autonomous Government of the Canton Saraguro.  Propose a manual of description, valuation and classification of posts to the Municipal Decentralized Autonomous Government of the Canton Saraguro. During the research development the Scientific, deductive, inductive, and historical methods were used, the bibliographical technique was used, an interview addressed to Mr. ex-mayor of GAD and a survey of 36 women and 130 men for a total of 166 officials and workers. And therefore it was possible to determine through the field results that officials and workers are not working according to their abilities and professional profile which to perform the various positions of the headquarters shall comply the requirements of the legal framework. After the collection, documentation analysis and talks with various direct GAD players and advice of the Minister of Labor Relations. I would detect that this institution does not have this guide for the proper distribution of human talent to which. I conclude that it is of real importance the implementation of the aforementioned manuAL